Evaluation of the correlation of faults with karstic springs in the mountain range of Prav Bisotun-Kermanshah - reza khoshraftar; gholam hassan jafari; mehdi feyzolahpour; habib arain tabar; Parvaneh moradi (تحقیقات کاربردی علوم جغرافیایی)
In this research, due to the abundance of tectonic and karstic structures in the Prav Bisotun region, the relation between fault building and karstic springs was evaluated. To do this, we first prepare information layers including the location of the springs, the location of the closed holes, faults, the slope and the elevation floor layer, and then the graph of the grains of the faults is drawn and weighted by the weight of the evidence Was investigated. Investigation of the relationship between springs and faults in the Prav Bistuon region using the weighted method showed that there is a close relationship between tectonic elements and the frequency of springs, so that at low distances of the faults, the number of springs more and with The distance from the fault, the number and frequency of springs, is reduced. Also, the results of diagrams showed that faults have a direct effect on the origin and orientation of the springs. In the study of the relationship between the slope and abundance of springs, it was found that most of the springs were located on a gradient of 0 to 5 percent and elevations of 1200 to 1400 meters. The above altitudes cover the mountain slopes.